Study of the essential oil composition of two subspecies of Abies cilicica (Ant. et Kotschy) Carr. from Turkey - Bagci, E; Baser, KHC; Kürkcüoglu, M; Babaç, T; Çelik, S (John Wiley & Sons Ltd, 1999)
The essential oil composition of two subspecies of Abies cilicica (taurus fir) from southern Turkey was investigated. CC-MS analysis of the oils of subsp. cilicica and subsp. isaurica from young shoots showed some qualitative and quantitative variations. Fifty-seven components were characterized in the oil of subsp. cilicica, with car-3-ene (14.2%), caryophyllene oxide (8.6%) and beta-caryophyllene (7.8%) as the major constituents. In the oil of subsp. isaurica, however, the major components among the 23 constituents identified were beta-pinene (29%), alpha-pinene (10%), eremophilene (9.3%) and beta-caryophyllene (8.8%). Morphological and chemical features of the two subspecies are discussed from a chemotaxonomic point of view. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: Abies cilicica subsp. cilicica; A-cilicica subsp. isaurica; Pinaceae; essential oil; car-3-ene; beta-pinene